Characterization of 3D angle-interlock thermoplastic composites under high strain rate compression loadings. (September 2017) - Bandaru, Aswani Kumar; Mittal, Vijay Kumar; Chouhan, Hemant; Asija, Neelanchali; Bhatnagar, Naresh; Ahmad, Suhail
Abstract: In the present work, dynamic compression response of polypropylene (PP) based composites reinforced with Kevlar/Basalt fabrics was investigated. Two homogeneous fabrics with Kevlar (K3D) and Basalt (B3D) yarns and one hybrid (H3D) fabric with a combination of Kevlar/Basalt yarns were produced. The architecture of the fabrics was three-dimensional angle-interlock (3D-A). Three different composite laminates were manufactured using vacuum-assisted compression molding technique. The high strain rate compression loading was applied using a Split-Hopkinson Pressure Bar (SHPB) set-up at a strain rate regime of 3633–5235/s. The results indicated that the dynamic compression properties of thermoplastic 3D-A composites are strain rate sensitive. In all the composites, the peak stress, toughness and modulus were increased with strain rate. However, the strain at peak stress of Basalt reinforced composites (B3D, H3D) decreased approximately by 25%, while for K3D specimens it increased approximately by 15%. The K3D composites had a higher strain rate as compared to the B3D and H3D composites. In the case of K3D composite, except strain at peak stress, remaining dynamic properties were lower than the B3D composite, however, hybridization increased these properties. The failure mechanisms of 3D-A composites were characterized through macroscopic and scanning electron microscopy (SEM).